A review of the level of good governance in international sport federations - Cabello-Manrique, D.; Puga-González, E. (Journal of Human Sport & Exercise, 2023)
The importance of increasing regulation in this field in all socio-economic areas, including the sport sector, and major pressure on the traditional autonomous hierarchical networks of the sport world done by governments, mainly due to the commercialisation of sport, have forced all major sports bodies and associations representing the sports industry to join this initiative of improving their good governance. A qualitative and quantitative study of the 35 Olympic ISFs has been carried out following the OGD - SGO index tool in 4 areas of improvement. The results allow to conclude that there is still a weakness in the control structures with a need to focus on the dimensions of democracy and checks and balances which are the weakest. There is also a lack of agreement on a standardised way to assess the good governance of sport entities that must be addressed and improved urgently.